61.4k views
5 votes
Solve for c. a (c – b) = d. d + ab OC= a OC = d - ab 6 d - ab O c = a ab - d о с — a​

1 Answer

3 votes

Answer:

Solving the equation
a (c -b) = d for c we get
\mathbf{c=(d+ba)/(a) }

Explanation:

We need to solve the equation
a (c -b) = d for c

Solving the given equation:


a (c -b) = d

Divide both sides by a


(a(c-b))/(a)=(d)/(a)\\c-b=(d)/(a)

Adding b on both sides


c-b+b=(d)/(a)+b\\c=(d)/(a)+b\\c=(d+ba)/(a)

So, solving the equation
a (c -b) = d for c we get
\mathbf{c=(d+ba)/(a) }

User Ryszard Szopa
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.